Understanding global changes of the mouse brain proteome after vaginal infection with HSV-2 using a label-free shotgun approach - Cheng, Jishuai; Wang, Qingzhen; Hu, Yiwen; Mou, Tangwei; Wang, Jianbin; Wang, Lichun; Zhang, Ying; Wang, Tinghua; Li, Qihan (Frontiers in Cellular and Infection Microbiology, 2022)
Herpes simplex virus type 2 (HSV-2) is a common human pathogen that establishes lifelong latency in neurons of the nervous system. The number of severe central nervous system infections caused by the virus has increased recently. However, the pathogenesis of HSV-2 infection in the nervous system is not fully understood. Here, we demonstrated global proteomic changes in the brain tissue in BALB/c mice vaginally infected with HSV-2. Data are available via ProteomeXchange with identifier PXD034186. A total of 249 differentially expressed proteins were identified in infected brain tissue. The GO and KEGG enrichment analysis of these proteins indicated that they were mainly involved in the regulation of synapse formation and synaptic excitability. In addition, genes affecting autophagy, the development of other neurodegenerative diseases, and signaling pathways relevant to other neurologic diseases were identified. Additional experiments, comparing the brain tissue of asymptomatic and symptomatic mice showed a differential expression of proteins involved in synapse formation and synaptic transmission. Others were involved in autophagy, addiction, and signaling pathways of other neurologic diseases. These results suggest that changes in synaptic structure and function, as well as autophagy, may be related to the development of neurologic abnormalities that follow HSV-2 infection. We also identified a protein GluN2A encoded by Grin2a was continuously expressed at high levels after infection. We propose that GluN2A may be a key molecule in the pathogenesis of HSV-2-induced neurologic diseases.